Surgical Impact of Coupling an Active Middle Ear Implant to Short Incus Process. Issue 6 (July 2018) - Schraven, Sebastian P.; Rak, Kristen; Cebulla, Mario; Radeloff, Andreas; Grossmann, Wilma; Hagen, Rudolf; Mlynski, Robert
Abstract : Introduction: Since 1996 the active middle-ear implant Vibrant Soundbridge (VSB) is used to treat mild-to-severe sensorineural hearing losses. The former standard surgical approach for incus vibroplasty included a mastoidectomy and a posterior tympanotomy, crimping the Floating-Mass Transducer (FMT) to the long incus process. The introduction of the short process (SP) coupler allows the attachment of the FMT to the incus body making the procedure of a posterior tympanotomy unnecessary. The aim of this study was to evaluate the duration of surgery (surgical case length) and to compare the audiological results of SP coupling with the former standard surgical approach to the long incus process. Materials and Methods: Patients undergoing an incus vibroplasty between October 2009 and February 2016 were included in this cohort study. The patients received an incus vibroplasty with crimping the FMT to the long incus process (former standard application) (n = 25) and with the SP coupler (n = 17) respectively. The surgical case length as well as the functional audiological outcome was assessed 12 months postoperatively using pure-tone audiometry and speech audiometry. Results: The surgical case length was significantly shorter in the SP coupler group compared to the standard application incus vibroplasty (85 ± 29 min vs. 114 ± 50 min). Additionally, patients receiving the SP coupler had an increased speech perception if compared to the standard application (Freiburger monosyllables at 65 dB SPL: 76.1 ± 16.1% vs. 66.2 ± 23.5%). Conclusion: The SP coupler leads to a shortened time of surgery and by the less invasive surgery to reduced risks for facial nerve and chorda tympani. Speech perception is significantly improved by SP coupling compared to classic long incus coupling.